Lives and Deaths of Werther : Interpretation, Translation, and Adaptation in Europe and East Asia - Johannes Kaminski (The British Academy, 2023)
Goethe's epistolary novel The Sorrows of Young Werther, first published in 1774, has produced a global echo that rivals contemporary bestsellers. While in the German context, the book was always outshined by its famous author, patriotic writers in Italy and China saw their lives mirrored in Werther's struggle, inspiring them to rewrite Goethe's novel in revolutionary terms. Meanwhile, French Romantics embraced Werther's expressive language to explore the dark corners of their souls. The same happened in Japan, where modernists invoked the text to show that'the most beautiful moment of life – that is, love – blossoms in the proximity of death.'Kaminski investigates how interpretations, translations, and literary adaptations of Goethe's novel have manipulated the text in ways that left deep marks on world literature.